Testing the efficacy of information transmission: is equity style index better than stock market index? - Lau, Wee-Yeap; Lee, Chin (Technical University of Liberec, 2015)
This paper examines the ability of equity style to predict future movement of composite leading economic index in a multivariate Granger causality framework. By comparing the efficacy of information transmission between equity style index and Bursa Malaysia Industrial Index, our results show that there is unidirectional causality from growth style to leading economic index. Second, there is also unidirectional flow from growth style to Bursa Malaysia Industrial Index. Third, there is a bidirectional relationship between growth style and KLCI broad market index. Finally, there is bidirectional causality between both growth style and value style. Further analysis from cross-correlation function reveals that growth style index is better than Bursa Malaysia Industrial Index. The former provides accurate and stronger cross-correlation with leading economic index. From these empirical evidences, it can be concluded that growth style index is a leading indicator which has more economic content than stock market index. It is better than stock market index in its efficacy of information transmission. The study brings to the awareness to policy makers and practitioners of the usefulness of equity style in constructing future leading economic index and early warning system of financial crisis.